TOO TIRED TO THINK STRAIGHT: THE IMPACT OF SLEEP DEPRIVATION ON DECISION-MAKING AND RISK-TAKING IN HEALTH SCIENCE STUDENTS (The Research of Medical Science Review, 2025)
Background: Sleep deprivation is a growing concern among health science students, particularly nursing students, due to their demanding academic and clinical schedules. Poor sleep quality and reduced sleep duration have been linked to impaired decision-making and increased risk-taking behavior two critical aspects that can influence patient safety and healthcare outcomes.Aim: This study aimed to assess the impact of sleep duration on decision-making ability and risk-taking tendencies among nursing students enrolled in different colleges in Swat.Methods: A cross-sectional study design was employed, involving 260 nursing students from multiple colleges in Swat. The sample was selected using a proportionate sampling technique, and the sample size was calculated using the Raosoft calculator based on a population of 800. Data were collected through a structured questionnaire that assessed sleep duration, decision-making performance, and risk-taking behavior. Ethical approval was obtained from the Institutional Review Board of Zalan College of Nursing, Swat. Data were analyzed using SPSS version 25, with descriptive statistics and ANOVA tests applied.Results: The findings indicated that students who reported sleeping ≥7 hours had significantly better decision-making scores (M = 7.42, SD = 1.25) and lower risk-taking scores (M = 4.26, SD = 1.43) compared to those sleeping 5–6 hours or less than 5 hours. The differences were statistically significant (p = 0.014 for decision-making, p = 0.031 for risk-taking).Conclusion: Adequate sleep duration positively influences decision-making and reduces risk-taking behavior in nursing students. Promoting sleep hygiene is essential for academic and clinical performance in healthcare education.